HUG Initiative: Overcoming roadblocks on a research career roadmap of individuals from historically marginalized or underrepresented genders - Lin, Mei-Yun; Chen, Hsinju; Golecki, Holly M. (Frontiers in Astronomy and Space Sciences, 2023)
The underrepresentation of students of Historically marginalized or Underrepresented Genders (HUGs) in STEM departments results in the low representation of HUG researchers in the space science community. This paper reviews relevant literature to explore the potential barriers that prevent HUG students from staying in STEM fields, including few opportunities to develop STEM identities, experiences with professional devaluation, and chilly campus climates. Thus, HUG students are more likely to feel excluded in STEM programs. To address the disparities, our HUG Initiative, a student-led research initiative, is proposed and piloted at a large research institution. This initiative promotes the pursuit of research careers among students who self-identify as HUG in the department of electrical and computer engineering. By holding panel discussions, interactive workshops, and networking luncheons, HUG Initiative aims to demystify what it means to be a researcher and provide resources on research opportunities and supports for HUG students. The influence on the HUG students' career choice and their accessibility of information will be evaluated by pre-study and post-study surveys. The research outcome will offer suggestions to create a safe and supportive departmental environment for HUG-identifying students to pursue research careers.